2018
DOI: 10.3389/fpls.2018.00963
|View full text |Cite
|
Sign up to set email alerts
|

The Binding Mechanism Between Inositol Phosphate (InsP) and the Jasmonate Receptor Complex: A Computational Study

Abstract: Jasmonates are critical plant hormones, mediating stress response in plants and regulating plant growth and development. The jasmonate receptor is a multi-component complex, composed of Arabidopsis SKP-LIKE PROTEIN1 (ASK1), CORONATINE INSENSITIVE 1 (COI1), inositol phosphate (InsP), and jasmonate ZIM-domain protein (JAZ). COI1 acts as multi-component signaling hub that binds with each component. InsP is suggested to play important roles in the hormone perception. How InsP binds with COI1 and the structural cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…We presume that this mechanism is followed in other stress conditions where other molecule plays a similar role. Similar analysis has been performed in the InsP interaction with the Jasmonate receptor [29]. In this study, it was observed that the binding of InsP with COI1 stabilises the conformation of COI1 and promotes the binding between JAZ1 and COI1.…”
Section: Discussionsupporting
confidence: 72%
“…We presume that this mechanism is followed in other stress conditions where other molecule plays a similar role. Similar analysis has been performed in the InsP interaction with the Jasmonate receptor [29]. In this study, it was observed that the binding of InsP with COI1 stabilises the conformation of COI1 and promotes the binding between JAZ1 and COI1.…”
Section: Discussionsupporting
confidence: 72%
“…JA is a phytohormone critical for environmental and pathogen defense signaling as well as plant physiology [68]. Similar to auxin signaling with TIR1, JA is also perceived by interactions between F-box protein, coronatine-insensitive 1 (COI1), and the JA zim domain (JAZ) transcriptional repressors [69][70][71]. JA gene regulation is modulated by JA-hormone binding to COI1 and the degradation of JAZ repressors, freeing repressed transcription factors to upregulate JA genes [67].…”
Section: How Do Pp-insps Function In Plants?mentioning
confidence: 99%
“…7 ). In this MD simulation, we used inositol octakisphosphate (InsP 8 ) instead of inositol pentakisphosphate (InsP 5 ) because previous reports showed that InsP 8 also formed stable complex with COI1- 2 -JAZ instead of phosphates (PO 4 ) 37 , 38 . In planta At JAZ9-selectivity of 2e was tested by using a GUS reporter assay using A. thaliana reporter lines, 35S: JAZ1-GUS , 35S: JAZ9-GUS , 35S: JAZ10-GUS , and 35S: JAZ12-GUS (Fig.…”
Section: Resultsmentioning
confidence: 99%